COVID-19 Infodemic: Media Ethics and the Challenges of Fake News - Hamdani, Sidi Sidi Mohamed; Housseine, Bachiri (Scholars' Journal, 2021)
This study investigated one of the main ethical challenges regarding the legitimate role of media in maintaining professional standards and ethics during the COVID-19 outbreak, with a focus on the case of Moroccan media. It principally deals with the conundrum of fake news spread in the midst of COVID-19 pandemic. In fact, it is apparent that there seems to be hardly an area left untouched by fake news regarding pandemic propagation. One should know that more attention has been drawn to the vulnerability of democratic societies to fake news and the ethical challenges brought by the pandemic to people across the globe.